PREDIKSI EROSI MENGGUNAKAN METODE USLE (Universal Soil Loss Equation) DI KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - Sastro, Diandra Sastriani Putri; Rahim, Yunnita; Pulogu, Siska Irhamnawati; Rahman, Rival (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
The erosion process can cause decreased soil productivity and fertility, reduce the soil’s carrying capacity for agricultural production, and reduce the quality of life. The study aimed to determine the erosion value predicted using the USLE and GIS methods, the tolerable erosion value (ETol), and to determine the direction of land use ini Pinolosian Subdistrict, South Bolaaan Mongondow Regency. The study was conducted in February – April 2024 in Pinolosian Subdistrict, South Bolaang Mongondow Regency, North Sulawesi Province. The study employed a descriptive method with a direct survey in the field by taking soil samples. Field observations and laboratory analysis results were used to calculate the predicted erosion value on cropland. Meanwhile, data was processed based on field observations and laboratory analysis results using the USLE method to obtain the predicted erosion value. The results of the study showed that the predicted erosion value using the USLE and GIS methods from the very light ones were found in SL 1 and 2 which were valued at 6.07 and 11.86 while the predicted erosion value which was very heavy was found in SL 9 which was valued at 643.62. The highest tolerable erosion value (ETol) was found in land unit 1 in Pinolosian District of 15.00 tons/ha/year. Land use directions that can be recommended based on erosion values ​​can be developed for food crops, horticulture and plantations depending on the slope conditions of each land.